From mesoscale to nanoscale mechanics in single-wall carbon nanotubes. (October 2017) - Torres-Dias, Abraao C.; Cerqueira, Tiago F.T.; Cui, Wenwen; Marques, Miguel A.L.; Botti, Silvana; Machon, Denis; Hartmann, Markus A.; Sun, Yiwei; Dunstan, David J.; San-Miguel, Alfonso
Abstract: The analysis of the radial collapse of individualized and isolated single-wall carbon nanotubes under high pressure as function of their diameter, d, distinguishes their mesoscale and their nanoscale mechanics. The evolution with pressure of the Raman spectra for nine tube chiralities and the theoretical modelling reveal a deviation from the continuum mechanics prediction of a collapse pressure P C ∝ d − 3 . Nanotubes show a normalized collapse pressure P N = P C d 3 = 24 α D ( 1 − β 2 / d 2 ) both in experiment and in very different theoretical models. In this expression β = 0.44 ± 0.04 nm represents the smallest diameter for a stable freestanding single-wall carbon nanotube and D is the bending stiffness of graphene. From the experimental data D = 1.7 ± 0.2 eV . Deviations from the continuum mechanics predictions start to be of significance for diameters smaller than ∼ 1 nm . The associated reduction of their collapse pressure is attributed to the discretization of the elastic compliances around the circumference of the tubes. Graphical abstract: